Assessment of liver fibrosis in primary biliary cholangitis: Comparison between indirect serum markers and fibrosis morphometry. Issue 3 (March 2016) - Stasi, Cristina; Leoncini, Luisa; Biagini, Maria Rosa; Arena, Umberto; Madiai, Stefania; Laffi, Giacomo; Marra, Fabio; Milani, Stefano
Abstract: Background: The accuracy of non-invasive methods for the quantification of liver fibrosis in primary biliary cholangitis (PBC) is still debated. Aims: To determine the histo-morphometric measurement of fibrotic tissue and to explore the possible association between indirect markers (APRI, FORNS, FIB-4, and Lok) and morphometry. Methods: Retrospective analysis of medical data from patients with PBC, on whom needle liver biopsy was performed as part of the diagnostic assessment. One section of each biopsy stained with Sirius red was used for calculating the percentage of collagen. Quantitative measure of fibrotic tissue (fibrosis morphometry) was calculated as a percentage of collagen content by digital image analysis. Morphometry results were divided into four groups reflecting Ludwig's staging and compared with values for indirect serum markers. Results: 50 PBC patients were enrolled (86% females, mean age 57 ± 12.30 years), 19 were Ludwig's stage I (38%), 14 stage II (28%), 12 stage III (24%), and five stage IV (10%). Morphometry results were significantly different among Ludwig stages ( p < 0.05). No significant differences were found for indirect serum markers. A significant correlation was found between morphometry results and indirect serum markers tested ( p < 0.05). Conclusion: In our cohort, the histo-morphometric values of fibrotic tissue increased progressively with Ludwig's stages of PBC, while non-invasive markers did not.